Determination of River Regime Coefficient and Water Storage Coefficient in Assessing Watershed Health in the Pacal Watershed, Bojonegoro - Sardana, Yuliani Wahyu (Sean Institute, 2025)
Watershed health is a crucial indicator of the watershed's ecological function and its capacity to provide sustainable environmental services. Environmental degradation due to anthropogenic activities such as land conversion in the Pacal watershed, Bojonegoro, has triggered an increase in the frequency of floods and droughts, indicating a critical decline in the watershed's hydrological function. This study aims to quantitatively evaluate the health level of the Pacal watershed through the analysis of two hydrological parameters River Regime Coefficient (KRS) and Water Storage Coefficient (KSA). The analysis results indicate that the hydrological condition of the Pacal Watershed falls into the poor category. The average KRS value during the 2013-2022 period was 282, classified as Very High. This very high KRS value indicates extreme discharge fluctuations and significant river flow instability, which have a high potential to trigger floods and droughts. Meanwhile, the average KSA value obtained was 0.057, classified as Poor. A very low KSA value indicates very limited infiltration and groundwater storage capacity, resulting in most rainwater becoming rapid surface runoff and minimal base flow during the dry season. Poor KRS and KSA values ​​indicate that the water regulation function of the Pacal Watershed has been critically degraded.